Two anaesthetic protocols and perioperative monitoring in a dog with asymptomatic right bundle branch block. - Flouraki, ES; Koutinas, C; Anagnostou, T; Savvas, I; Kazakos, G (Journal of the Hellenic Veterinary Medical Society, 2025)
A 16-year-old mixed breed dog was presented for skin mass excision. During initial evaluation, a right bundle branch block and a mitral valve insufficiency were detected, while concentration of cardiac troponin-I (cTnI) was slightly elevated at 0.653ng/ml. The dog was anesthetized with fentanyl and propofol, maintained with isoflurane and a ring block of lidocaine was also performed. Anaesthesia and peri-operative monitoring was uneventful, while post-operative concentration of cTnI was elevated at 1.34 ng/ml. The following day a partial urethral obstruction was noted, and the dog was rescheduled for cysteotomy and urethrostomy to avoid complete obstruction. The second anaesthetic protocol consisted of fentanyl, midazolam and etomidate for induction and isoflurane for maintenance with the addition of fentanyl as a constant rate infusion. Anaesthesia and perioperative monitoring were also uneventful. Post-anaesthetic evaluation revealed an increased cTnI plasma concentration at 2.57 ng/ml. Ten days later, during re-examination, the plasma concentration of cTnI had returned to normal and no deterioration was noted on ECG examination. Four months later, the patient’s physical status and ECG examination indicated no further dysfunction of the heart.